Methods for geopolymer formulation development and microstructural analysis - Van Riessen, Arie; Rickard, William; Williams, R.; Van Riessen, G. (2017)
© 2017 Göller Verlag. Alkali-activated materials (AAMs) and geopolymers have been extensively studied, although widespread commercialisation has been hampered, in part, by the use of precursors that are rarely homogeneous and are generally poorly characterised. Even when precursors are well characterised, their extent of reaction during geopolymer synthesis is not well known, leading to a disparity between targeted and actual compositional ratios. Small variations in compositional ratios, particularly Si:Al, can lead to dramatic changes in physical properties. A process for characterising precursors, focussing on their reactive component, will be described here, followed by methods that can be used to determine the extent of reaction in the final product. Characterising the final product is important, but it does not reveal what processes occur between mixing the precursors and setting of the solid geopolymer.We will also describe a method that can be used to track dissolution of precursors and subsequent evolution of the alkali-activated product, thus providing amore comprehensive picture of geopolymerisation. This paper demonstrates a link between precursor characterisation and the extent of reaction in order to provide those working with alkali-activated materials with additional knowledge enabling them to manufacture reproducible, high-quality products.